2014
DOI: 10.1177/0255761413515814
|View full text |Cite
|
Sign up to set email alerts
|

Drawing a line in water: Constructing the school censorship frame in popular music education

Abstract: The apparent ideological tensions between popular musics and formal school contexts raise significant issues regarding teachers' popular repertoire selection processes. Such decision-making may be seen to take place within a school censorship frame, through which certain musics and their accompanying values are promoted, whilst others are suppressed. Through semi-structured interviews with five Finnish music teachers, the narrative instrumental case study reported in this article aims to explore secondary scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 30 publications
0
37
0
1
Order By: Relevance
“…Other critical angles include reflections on the shifting authenticities in Scandinavian music education, from, among other things, valuing formally acquired musical knowledge and skills to celebrating and rewarding 'students' autonomy' (109) and even considering '[the] corresponding lack of teacher control as positive criteria for the evaluation of a good result' (109; see also Zandén 2010). Kallio (2015), on the other hand, is concerned with Finnish compulsory school music teachers' popular repertoire selection processes in a school and curricular context where 'all musics' are seemingly welcomed, and where 'teachers … are afforded considerable freedoms in selecting popular repertoire ' (195). Building largely on a sociological theoretical framework, she aims to construct what she terms 'the school censorship frame (195), in other words mapping the societal forces that frame and "influence teachers" decisions to include or exclude popular musics ' (197).…”
mentioning
confidence: 99%
“…Other critical angles include reflections on the shifting authenticities in Scandinavian music education, from, among other things, valuing formally acquired musical knowledge and skills to celebrating and rewarding 'students' autonomy' (109) and even considering '[the] corresponding lack of teacher control as positive criteria for the evaluation of a good result' (109; see also Zandén 2010). Kallio (2015), on the other hand, is concerned with Finnish compulsory school music teachers' popular repertoire selection processes in a school and curricular context where 'all musics' are seemingly welcomed, and where 'teachers … are afforded considerable freedoms in selecting popular repertoire ' (195). Building largely on a sociological theoretical framework, she aims to construct what she terms 'the school censorship frame (195), in other words mapping the societal forces that frame and "influence teachers" decisions to include or exclude popular musics ' (197).…”
mentioning
confidence: 99%
“…However, when acknowledging the musical tastes of one student, teachers may be in turn excluding another. In a study of five Finnish music teachers, Kallio (2015) identified a “school censorship frame, through which certain musics and their accompanying values are promoted, whilst others are suppressed” (p. 197). She wondered how Finnish music teachers construct and navigate this censorship frame.…”
Section: Pedagogical Approachesmentioning
confidence: 99%
“…A variety of pedagogical approaches are shown to exist in multiple settings. Student-centered and autonomous groups can work together to accept and incorporate a variety of ideas and pedagogies, but tensions still emerge because “while encouraging democratic participation in music education, teachers must also justify decisions regarding whose music is excluded” (Kallio, 2015, p. 196). As teachers make pedagogical decisions about popular music, they also have to navigate curricula that addresses learning outcomes.…”
Section: Curriculummentioning
confidence: 99%
“…When did we do rightly whenever we felt we needed to protect and teach only some specific genres of music and their respective pedagogies (Allsup 2015;Kratus 2007;Bradley 2006;Green 2008)? When did we do justice to the massive array of music making and learning experiences by censoring (Dyndahl and Nielsen 2014;Kallio 2014) the repertoire, or by managing (hooks 1992, 354), tolerating (Matthews 2015;Hess 2013), arranging and simplifying the authentic and diverse musical experiences into ready-made and ready-to-use packages of music learning (Hess 2015, Wasiak 2009, Bradley 2006, Banks 1994? A case in point was illustrated by one of the graduate students in Bradley, Golner, and Hanson (2007): I think about the curriculum I teach-I'm going to have to do major work to get where I need to be in the world and United States cultural knowledge levels to teach anything besides European and Jazz musical history … areas to bone up on … current pop music, the history of rock and blues and funk and rap etc….…”
Section: During My Graduate Studies In the United States I Could Onlmentioning
confidence: 99%